Network Activity Monitoring Against Malware in Android Operating System - Luis Miguel Acosta-Guzman; Gualberto Aguilar-Torres; Gina Gallegos-Garcia (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Google’s Android is the most used Operating System in mobile devices but as its popularity has increased hackers have taken advantage of the momentum to plague Google Play (Android’s Application Store) with multipurpose Malware that is capable of stealing private information and give the hacker remote control of smartphone’s features in the worst cases. This work presents an innovative methodology that helps in the process of malware detection for Android Operating System, which addresses aforementioned problem from a different perspective that even popular Anti-Malware software has left aside. It is based on the analysis of a common characteristic to all different kinds of malware: the need of network communications, so the victim device can interact with the attacker. It is important to highlight that in order to improve the security level in Android, our methodology should be considered in the process of malware detection. As main characteristic, it does not need to install additional kernel modules or to root the Android device. And finally as additional characteristic, it is as simple as can be considered for non-experienced users.